Aromatic CC Bonds as Dipolarophiles: Facile Reactions of Uncomplexed Electron‐Deficient Benzene Derivatives and Other Aromatic Rings with a Non‐Stabilized Azomethine Ylide. Issue 22 (3rd April 2013) - Lee, Sunyoung; Diab, Sonia; Queval, Pierre; Sebban, Muriel; Chataigner, Isabelle; Piettre, Serge R.
Abstract Non‐stabilized azomethine ylide 4 a reacts smoothly at room temperature with a variety of uncomplexed aromatic heterocycles and carbocycles on the condition that the ring contains at least one or two electron‐withdrawing substituents, respectively. Aromatic substrates, including pyridine and benzene derivatives, participate as 2 π components in [3+2] cycloaddition reactions and interact with one, two, or three equivalent(s) of the ylide, depending on their structure and substitution pattern. Thus, this process affords highly functionalized polycyclic structures that contain between one and three pyrrolidinyl ring(s) in useful yields. These results indicate that the site selectivity of the cycloaddition reactions strongly depends on both the nature and the positions of the substituents. In most cases, the second 1, 3‐dipolar reaction occurs on the opposite face to the one that contains the first pyrrolidinyl ring. DFT calculations on model compounds indicate that a concerted mechanism features a low activation barrier.